Knowledge management in family firms: a systematic review, integrated insights and future research opportunities. Issue 2 (13th September 2021) - Su, Emma; Daspit, Joshua
Abstract : Purpose: The literature related to knowledge management (KM) is robust with respect to insights regarding firms in general. However, less is known about the KM of family firms despite these firms being the most common form of business organization worldwide. Further, even though the number of studies examining family-firm KM has increased in recent years, the insights gained remain fragmented. Therefore, the purpose of this study is to help coalesce and advance the study of family-firm KM. Design/methodology/approach: In pursuit of these goals, a systematic literature review was conducted. Using a 6-step, systematic literature review protocol, 74 articles focused on family-firm KM published in 23 journals were identified and reviewed. Findings: This literature review contributes to the synthesis and advancement of family-firm KM scholarship in several ways. First, key factors and relationships are identified and integrated into a robust framework. Second, scholarly insights are synthesized, and a review of the primary antecedents, outcomes and moderating factors associated with family-firm KM processes is presented. Third, promising opportunities for future research are highlighted to advance family-firm KM scholarship. Originality/value: With a focus on reducing the fragmentation in the literature, this review synthesizes insights related to the most commonly studied antecedents, outcomes and moderators associated with family-firm KM. Additionally, antecedents are organized and reviewed according to the nature of their influence on family-firm KM processes, highlighting the simultaneous opposite effects of some influences. Further, key outcomes are synthesized based on their family versus firm-centric orientation. Even further, insights and opportunities focused on advancing the theory, antecedents, outcomes, moderators and other issues related to family-firm KM are presented in an effort to support the continued progress of scholarship in this area.